Infective Endocarditis Related to Unusual Microorganisms: A Prospective Population-Based Study. (13th April 2020) - Limonta, Silvia; Cambau, Emmanuelle; Erpelding, Marie-Line; Piau-Couapel, Caroline; Goehringer, François; Plésiat, Patrick; Revest, Matthieu; Vernet-Garnier, Véronique; Moing, Vincent Le; Hoen, Bruno; Duval, Xavier; Tattevin, Pierre; et al.
Abstract: Background: Increased access to heart valves through early surgery and progress in molecular microbiology have reduced the proportion of infective endocarditis (IE) with no microbiological documentation and increased the proportion of IE associated with unusual microorganisms. Methods: We performed an ancillary study of a large prospective population-based survey on IE. Unusual-microorganism IE was defined as definite IE (Duke-Li criteria) due to microorganisms other than streptococci, staphylococci, or enterococci. Results: Of 471 cases of documented IE, 46 (9.8%) were due to unusal microorganisms; the following were involved in >1 case: Candida albicans (n = 4), Cutibacterium acnes (n = 4), Pseudomonas aeruginosa (n = 3), Cardiobacterium hominis (n = 3), and Coxiella burnetii (n = 2). Cases were documented with blood cultures (n = 37, 80.4%), heart valve polymerase chain reaction (PCR; n = 5), heart valve culture (n = 2), PCR on vertebral biopsy (n = 1), or serology (n = 1). As compared with IE due to staphylococci, streptococci, or enterococci (n = 420), IE due to unusual microorganisms occurred more frequently in patients with previously known heart disease (69.0% vs 44.3%; P = .002), prosthetic valve (40.5% vs 18.1%; P = .0006), longer duration of fever (mean, 35.1 ± 46.8 days vs 12.5 ± 17.8; P = .003), and who were more often nosocomial (38.1% vs 20.2%; P = .02). Conclusions: In this population-based study, 9.8% of IE cases were due to unusual microorganisms, with a predominance of anaerobes, yeast, and gram-negative bacilli. As compared with IE related to staphylococci, streptococci, or enterococci, IE cases related to unusual microorganisms were associated with previously known heart disease, prosthetic valve, longer duration of fever, and nosocomial acquisition. Trial registration: ORCID 0000-0003-3617-5411 Abstract : In this population-based study, 10% of endocarditis were due to microorganisms other than staphylococci, streptococci, and enterococci. These included anaerobes, yeasts, or Gram-negative bacilli, with an increased risk in patients with heart disease, prosthetic valve, prolonged fever, and nosocomial endocarditis.